PERCEPTIONS AND EFFECTS THE ECONOMIC OF MOUNT KELUD TOURISM SITE DEVELOPMENT POST-ERUPTION TO THE LOCAL FARMERS - Sigit Dwi Nugroho; Setyo Parsudi (UNEJ e-Proceeding, 2017)
Tourism has proven itself to be able to support the economic growth through opportunity for investation, occupation, work, business which accumulated in the prosperity of the people. Since re-open, the effect of the development of Mount Kelud tourism post-eruption aren’t clearly identifiable. Given that reason, the goals of this research are to: 1). Identify the locals farmers’ perception about the development of Mount Kelud tourism post-eruption which include its process and development. 2). Identify the effects of post-eruption Mount Kelud tourism development to the local farmers which include occupation-changes, working hours, per-family income, land price, price of the daily needs, local product values. The research conclude that; 1) local farmers’ perception in Sugihwaras village to the development of the posteruption Mount Kelud tourism are generally positive and they mostly agree with the tourism site’s existence. 2) from the ecenomic aspect, the post-eruption Mount Kelud tourism site has significant effects to the rise of land selling price and type of jobs/occupation and the income of the local farmers who work on the tourism site. But it doesn’t significantly affected the working hours, the price of daily needs and other local products.